Pendampingan Analisis Perhitungan Harga Pokok Produksi Industri Bagi Pengusaha Gula Semut di Desa Belitar Seberang Kecamatan Sindang Kelingi Kabupate Rejag Lebong - Eska Monique Prima Damarsiwi; Karona Cahya Susena; Nenden Restu Hidayah; Abdul Rahman; Muhammad Roky Pratama (Universitas Dehasen Bengkulu, 2023)
This community service aims to provide assistance in analysing the calculation of cost of goods produced in the ant sugar processing business in Belitar Seberang Village, Sindang Kelingi District, Rejang lebong Regency. The mentoring method includes socialisation, training and direct mentoring to ant sugar entrepreneurs. The objective of this mentoring programme is to assist the palm sugar entrepreneurs in determining the cost of production and identifying factors that affect the cost of production.The results of the mentoring programme show that the cost of goods produced by palm sugar entrepreneurs in Belitar Seberang Village can be influenced by several factors such as raw material costs, labour costs, production costs, and so on. To reduce the cost of production, ant sugar entrepreneurs can carry out several strategies such as optimising the use of raw materials, improving the production system, and negotiating with suppliers.The conclusion of this research is that the assistance programme for calculating the cost of goods produced in the ant sugar processing business in Belitar Seberang Village has provided benefits for ant sugar entrepreneurs in the area. By knowing the cost of goods produced and the factors that affect the cost of goods produced, ant sugar entrepreneurs can make more effective decisions in managing their business. In addition, the results of this study are also expected to contribute to the development of the ant sugar industry in Indonesia as a whole.